PERTANIAN TRADISIONAL: PERUBAHAN PERILAKU PETANI PADI DESA MEKARJAYA, KECAMATAN KIARAPEDES, KABUPATEN PURWAKARTA - Heryanto, Mahra Arari; Nugraha, Adi (Universitas Galuh, 2023)
Green revolution have made many changes to traditional agriculture from prioritizing local inputs to becoming dependent on high-cost external input. Various environmental, social and economic damages are unavoidable in these changes. This paper aimed to examine traditional agricultural practices that are still being implemented and how its impact socially and economically. The method is a quantitative design by measuring the farmers behavior in Mekarjaya Village, Kiarapedes District, Purwakarta Regency. Measurements were made with a Likert scale and analyzed using Rasch modeling. The findings of this study indicate that there has been a change in farmer behavior from traditional to modern agricultural practices, which is triggered by significant differences in productivity. The traditional agricultural practices that are still being done are only traditions or rituals that do not affect aspects of rice production. Socio-economically, impact of these changes is an increase in the level of vulnerability of rice due to high dependency and a slowly degraded environment. Farmers' indogenous knowledge has been depreciated by modern knowledge and practices that are highly dependent on external resources. The positive impact of modern agriculture has consequences for a high vulnerability to environmental and economic risks faced by farmers.